2018
DOI: 10.15282/jmes.12.2.2018.15.0327
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behavior of short-cut aramid fiber reinforced SBR elastomers: the effect of fiber orientation

Abstract: Elastomeric materials are widely used in daily applications, such as conveyor belts and wiper. Generally, elastomeric materials show poor tribological behavior. Adding fibers to an elastomer is a way to solve this problem. The orientation of the fibers influences the mechanical and tribological behavior of the elastomers. In the present study, the effect of shortcut aramid fiber orientation on the tribological behavior for a Styrene-Butadiene Rubber (SBR) was examined. Three types of compounds which have diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Later, Rodriguez [18] showed that by adding short-cut aramid fibers into the elastomers leads to the reduction of the coefficient of friction. In a previous study, the effect of fiber orientation on the tribological behavior of short-cut aramid fiber reinforced elastomers has been reported [19]. It is concluded that the steady-state coefficient of friction are the same for all reinforcement directions due to the presence of fibers on the wear surface.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Later, Rodriguez [18] showed that by adding short-cut aramid fibers into the elastomers leads to the reduction of the coefficient of friction. In a previous study, the effect of fiber orientation on the tribological behavior of short-cut aramid fiber reinforced elastomers has been reported [19]. It is concluded that the steady-state coefficient of friction are the same for all reinforcement directions due to the presence of fibers on the wear surface.…”
Section: Introductionmentioning
confidence: 88%
“…In a previous study, it has been reported that the steady-state coefficients of friction of 15 phr short-cut aramid fiber reinforced elastomer (composite 1) for several reinforcement directions show the same values although the mechanical properties of these composites are different [19]. To gain a better understanding of that findings, the wear processes of composite 1 and its relation to friction during sliding contact is studied.…”
Section: Experimental Methodsmentioning
confidence: 98%
“…It can be seen that the steady-state coefficients of friction of those composites decrease to approximately 4 times lower than that at the beginning of the tests. The reason of this phenomenon is that a part of the fibers are sticking out of the composite and they are present on the wear surface [16,17]. It leads to a reduction of the real contact area between the counter surface and the composite.…”
Section: Mechanical Properties Of the Materialsmentioning
confidence: 99%
“…4(a). In a previous article [16], it was shown that the coefficient of friction of elastomers that are reinforced with a high amount of short-cut aramid fibers is controlled by the fibers on the wear surface rather than by the bulk properties. Since the counter surface is mainly in contact with the fibers, the steadystate coefficients of friction of composite 15 SF at both contact pressures have a uniform value.…”
Section: Effect Of Contact Pressurementioning
confidence: 99%
“…Natural rubber (NR) is the most important elastomer and it is used extensively in many applications due to its high elasticity (reversible deformability) [1][2][3][4][5][6][7][8][9]. Natural rubber is extracted in the form of latex from the Hevea brasiliensis tree.…”
Section: Introductionmentioning
confidence: 99%